SASTRA LISAN BERBASIS INDUSTRI KREATIF: RUANG PENYIMPANAN, PENGEMBANGAN, DAN IDENTITAS - Anoegrajekti, Novi; Macaryus, Sudartomo (Balai Bahasa Jawa Timur, 2018)
This paper aims at explaining the development of creative industry-based oral literature. Banyuwangi's oral literature has autonomously developed along with tradition and modern arts, such as janger, fashion, dance, and song. The use of ethnographic method began with an inventory of bibliographic data and was supplemented by field data through interviews, observations, and participation. The story of Sri Tanjung Sidopekso becomes the janger play and theme of Banyuwangi Ethno Carnival. The mantra of jaran goyang is transformed into dance and song. Various creative industries have the potential as a source of reconstructing oral literature. In coastal societies there has developed oral literature related to maritime culture. In Muncar Banyuwangi, the rituals of petik laut use spells and maritime cultural symbols, such as mantras, pilgrimages to the tombs of the founders of the Muncar fishing village. While in Payangan Jember, the story of the founders of the fishing village is respected by singing macapat babad Marsodo. All that has a meaning when it becomes action, knowledge, experience, and appreciation of the supporting community. The results show that oral literature has the potential to inspire the creative industries. Likewise reversely, creative industries have the potential as a source for reconstructing oral literature that enriches their forms and versions.